Analysis of Locutionary, Illocutionary and Perlocutionary Speech Acts in Youtube Ads - Aklilah Zahirah; Intan Sari Ramdhani (CV. Rayyan Dwi Bharata, 2023)
In the digital era, communication media are very diverse and fast in conveying messages. One of them is social media that has an important role in language development, namely YouTube. Apart from functioning as a social media for watching videos, YouTube functions to earn income for YouTubers. This income is obtained through advertisements contained in videos on several YouTube channels. Ads are texts that persuade the reader to do something according to the message in the ad. Advertising is one type of communication or also known as speech act. Speech acts have three types, namely locutionary, illocutionary, and perlocutionary. This research uses a descriptive qualitative method with the listening method. The data source in this study was obtained from YouTube advertising videos. The data in this study were obtained from trending videos with different account channels. Based on the research that has been done, 14 utterances were found in the five videos, namely, shopee candy ads, aqua ads, gopay ads, tea shoots ads, garnier ads, and head and shoulders shampoo ads. Based on the findings, the most violations were found in illocutionary speech acts. This is consistent with findings which show that producers of goods or services use sentences that are not convoluted and have clear meanings. The use of these sentences aims to make people understand and catch the meaning of the speech easily